The morphogenesis of erosional valleys in the slopes of the Drwęca valley and the properties of their colluvial infills - Karasiewicz, Tomasz; Tobojko, Lucyna; Świtoniak, Marcin; Milewska, Kinga; Tyszkowski, Sebastian (Bulletin of Geography. Physical Geography Series, 2019)
The article characterises Late Glacial and Holocene deposits and provides a morphometric analysis of erosional and denudation valleys in the slope and terraces of the Drwęca Valley near Jajkowo village, a few kilometres east of Brodnica. A detailed field mapping was used to identify in detail two such forms within the western slope of the Drwęca Valley. Based on the results, it was found that the longitudinal profiles of these forms are not aligned (with an inclination of approximately 4˚). The slopes of valley I are asymmetrical, with the southern slope being milder than the northern exposure, which is not the case with form II. Form I is narrower and has a V-shaped cross profile, while II is wider and has a trough-shaped profile cross profile. The side valleys were initially cut by the flow of what were most probably meltwaters and precipitation water from the moraine plateau, then the erosion stopped and the valleys gradually filled and widened mainly as a result of rinsing and mass movements, which may have been increased by man. Currently, forestry use is significantly reducing the activity of slope processes and rinsing. The sediments that fill the bottoms of these forms are usually consist of silt or sandy lithofacies with massive, streaky or deformation horizons. They are characterised by a significant enrichment in organic matter which is typical for colluvial deposits of young glacial areas. The relatively high pH values result from the investigated erosional forms intersecting into sediments rich in calcium carbonate. Moreover, groundwater flowing from the moraine plateau may also be the source of basic components.